2014
DOI: 10.1111/age.12255
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the porcine miR‐208b is associated with microRNA biogenesis and expressions of SOX‐6 and MYH7 with effects on muscle fibre characteristics and meat quality

Abstract: MicroRNAs (miRNAs) encoded by the myosin heavy chain (MHC) genes are muscle-specific miRNAs (myomiRs) and regulate the expression of MHC isoforms in skeletal muscle. These miRNAs have been implicated in muscle fibre types and their characteristics by affecting the heterogeneity of myosin. In pigs, miR-208b and miR-499 are embedded in introns of MYH7 and MYH7b respectively. Here, we identified a novel single nucleotide polymorphism (SNP) in intron 30 of MYH7 by which porcine miR-208b is encoded. Based on the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Our previous studies revealed that skeletal muscle-specific miRNAs, namely miR-1, miR-133a/b, miR-206, miR-208a/b, miR-496, and miR-499, were abundant in the muscles of JB cattle [4], whereas none of them was detected in the plasma profiles except for a modest miR-486 content [24]. In contrast, the plasma samples were enriched with moderate concentrations of miRNAs associated with adipose tissue, such as miR-15a, miR-19a/b, miR-21, miR-27b, miR-92a/b, miR-103, miR-106a/b, miR-107, miR-125b, and miR-150 [11,12]. It is especially notable that the bovine-specific miR-1584-5p, miR-2305, miR-2412, and miR-2478, most of which are associated with energy metabolism [32], were highly enriched in the plasma samples of both groups in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies revealed that skeletal muscle-specific miRNAs, namely miR-1, miR-133a/b, miR-206, miR-208a/b, miR-496, and miR-499, were abundant in the muscles of JB cattle [4], whereas none of them was detected in the plasma profiles except for a modest miR-486 content [24]. In contrast, the plasma samples were enriched with moderate concentrations of miRNAs associated with adipose tissue, such as miR-15a, miR-19a/b, miR-21, miR-27b, miR-92a/b, miR-103, miR-106a/b, miR-107, miR-125b, and miR-150 [11,12]. It is especially notable that the bovine-specific miR-1584-5p, miR-2305, miR-2412, and miR-2478, most of which are associated with energy metabolism [32], were highly enriched in the plasma samples of both groups in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, skeletal muscle miR-206 and miR-208b expression is temporally upregulated, accompanying the downregulation of myosin heavy chain 2x expression, in grazing Japanese Shorthorn (JSH) cattle whereas the expression did not change in housed [7]. Since muscle physiological property determined by the muscle type have impacts on meat quality [810], potential association of miRNAs with muscle gene expression and mat quality have been focused recently [1113]. Besides skeletal muscle, transcriptomic miRNA analyses in mammalian adipose tissue have unveiled their roles in fat accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in contrast to the results of our and Kim et al (2015) studies and may be associated with the different age of pig used in the experiments. In our study, as well as in the experiment of Kim et al (2015) pigs were at the slaughter age, however in the study of Komatsu et al (2016) animals aged 23 days. Moreover growth rate groups were selected based on the expected breeding value not direct phenotypic data.…”
Section: Resultsmentioning
confidence: 60%
“…Highest values for these traits were noticed in GG genotypes (P ≤ 0.05 or P ≤ 0.01). Kim et al (2015) in previous study showed that AA genotype is associated with highest expression of MYH7 gene in the longissimus dorsi muscle tissue of Berkshire pigs. Komatsu et al (2016), however, stated that high expression of MYH7 gene in longissimus dorsi is associated with extremely low growth rate in Landrace pigs.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation